Reversible human-temperature-responsive luminescence switching in a Mn(ii)-based metal halide. Issue 4 (13th January 2023) - He, Zi-Lin; Wei, Jun-Hua; Luo, Jian-Bin; Zhang, Zhi-Zhong; Kuang, Dai-Bin
Abstract : The reversible phase transition with luminescence switching can be realized by simply laying hands on the (TMS)2 MnBr4 powder. Furthermore, it exhibits promising potentials in portable anti-counterfeiting, thermal imaging, and rewritable PL paper. Abstract : The flexibility afforded by their modular structure confers fruitful unique properties to organic–inorganic hybrid metal halides (OIMHs). Typically, stimuli-responsive materials have wide applications in thermal imaging, thermometry, and anti-counterfeiting. Herein, the Mn(ii )-based OIMHs (TMS)2 MnBr4 (TMS = trimethylsulfonium) were prepared through a facile dry ball-milled method. The obtained ball-milled powders show an intriguing phase transition along with emission switching. Importantly, photoluminescence (PL) switching can be realized by simply laying hands on the (TMS)2 MnBr4 powders, highlighting their promising application potential in portable thermosensitive devices.